The development of a globally acceptable national model for occupational hygiene in Turkey: a modified Delphi study - Sibel Kiran; Alp Ergor; Ceyda Sahan; Esra Emerce; Sergio Luzzi; Yucel Demiral (BMC, 2019)
Abstract Background Although various organizations working in developed countries established the standards and approaches used in occupational hygiene, occupational hygiene professional interests and needs continue to develop in a global context. There is thus an urgent need for expanded occupational hygiene models. For successful field implementation, these models should be based on several sets of criteria, including those related to international standards, various national requirements, and multidisciplinary approaches. This is particularly important for countries in which no occupational hygiene model has been developed. This study thus examined the consensus on occupational hygiene standards among stakeholders in Turkey regarding the development of a national model. A modified Delphi study was conducted among key occupational health experts in Turkey who could aid in the relevant implementation, policy-making, and educational processes for such a model. Participants were selected from various governmental institutions, non-governmental organizations, trade unions, universities, and occupational health practices. Results The first-round findings were obtained from open-ended questions. The results revealed several requirements, including the adoption of an international hygiene definition, the official recognition of professional and practical areas in Turkish occupational hygiene, hygienist training methods, priorities, and competent institutions. Second-round findings indicated a consensus rate of over 80% regarding the need for implementation standards, training and education standards, requirements and priorities, and competent institutions for professionals working in the field of occupational hygiene. A third-round and SWOT analysis was also conducted among the group to confirm the consensus issues. Conclusions The search for solutions and developmental expectations increases when awareness of internationalization and the need for common global standards increase. This developmental process may provide the basis for an appropriate model in developing countries.